PESAN DALAM FILM BUAH HATI MAMA - Suhardi Suhardi (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2021)
At this article, the author attempted to uncover the message that is conveyed in the movie of "Buah Hati Mama". The movie of "Buah Hati Mama" as a medium of mass communication parse the message by using the language of film, mainly through the way the story is supported by other elements, such as; setting, property, actors, effects, and lighting. Message in the film is easy to understand because of the logical setting, support of lighting, the complements of property, dramatic effect, and the actors who animate the character. Film is a powerful medium to convey the message to the audience because it may touch the psychological element of the audience. Crew's expertise in designing cinematic and narrative element is a force to be optimized.